The restoration of castle De Haar in Haarzuilens (Bulletin KNOB, 1996)
This article deals with the restoration of the medieval castle De Haar near Utrecht, which started in 1892. Particularly the old courtyard draws one's attention. In the late summer of 1890 the Dutch architect P.J.H. Cuypers was involved in the early plans for a restoration of the ruins of castle De Haar, which in 1890 was inherited by Baron Etienne van Zuylen van Nijevelt, who had married the French Baroness Hélène de Rothschild in 1887. In September 1891 Cuypers and his son Joseph sent the first plans for the restoration to Van Zuylen.Besides the two official reasons for the restoration of the ruins (i.e. to have a holiday home in August and respect for the social and political history of the Van Zuylen family) there was probably another reason: a close connection between the grandparents of Hélène de Rothschild and the French emperor Napoleon III and his wife Eugénie de Montijo. By order of this couple the architect Viollet-le-Duc restored the castle Pierrefonds in France, and to Baron Etienne this castle was an important example for his ruins in The Netherlands.In the execution of the work the old medieval courtyard was covered by a barrelvault, constructed of cast iron, concrete and slates. In the interior of the house the vault was decorated with a gold-painted finish of wood. It is interesting that Cuypers and his son made a number of models of the Hall to show the Baron the various possibilities for this space. A few models have been saved and are in possession of the Stedelijk Museum Roermond. In 1897 the vault was nearly finished. The Hall is still one of the most attractive rooms of the castle.